The Moment of truth – trancesding knowledge through myriads of creativity / Izaddin Matrahah - Izaddin, Matrahah (Universiti Teknologi MARA, Perak, 2019)
The arts as in the sciences are an effort of creating and participating in a sort of ritualistic behaviour were the artist or the creator, trying to initiate certain kind creation in every sense that is pleasing to the artists themselves or produce an artwork that can communicate to the general public as a whole or even to the world maybe. As in the words of Alvaro Castagnet a world renowned watercolourist on the topic of art: “Art is not about intellectuality but rather about jumping into the unknown”.